Inertial spontaneous symmetry breaking and quantum scale invariance - Ferreira, PG; Hill, CT; Ross, GG (American Physical Society, 2018)
Weyl invariant theories of scalars and gravity can generate all mass scales spontaneously, initiated by a dynamical process of “inertial spontaneous symmetry breaking” that does not involve a potential. This is dictated by the structure of the Weyl current, K μ , and a cosmological phase during which the Universe expands and the Einstein-Hilbert effective action is formed. Maintaining exact Weyl invariance in the renormalized quantum theory is straightforward when renormalization conditions are referred back to the VEV’s of fields in the action of the theory, which implies a conserved Weyl current. We do not require scale invariant regulators. We illustrate the computation of a Weyl invariant Coleman-Weinberg potential.